Determinants of Breast Cancer Knowledge and Screening Practices among Women of Childbearing Age in Abakaliki Metropolis, Nigeria: a Cross-Sectional Study. - Ossai, Edmund; Ezenwosu, Ifeyinwa; Essuman, Odeamuza; Nwekpa, Constance; Eze, Irene (Journal of Midwifery & Reproductive Health, 2025)
Background & aim: Breast cancer is a public health concern and the leading cause of death among women. This study examined the factors affecting knowledge of breast cancer and screening practices among women of childbearing age in Abakaliki, Metropolis, Nigeria. Methods: The community-based, cross-sectional study was carried out on 401 women using a four-stage sampling process from February to March 2021 in Abakaliki Metropolis, Nigeria. The tools used consisted of a questionnaire including socio-demographic and breast disease-related data, and a researcher- made questionnaire for knowledge and Preventive practice against breast cancer that was completed by face-to-face method in the community. Data were analysed by SPSS version 25 using descriptive and inferential statistics. Results: The results showed that 18.0% of respondents had good knowledge and 8.7% had good breast cancer screening practices, from whom 23.4% had ever practiced breast self-examination, 9.5% had undergone a clinical breast examination, 3.5% had undergone mammography. Determinants of good knowledge of breast cancer included having an interest in matters related to breast cancer, AOR= 4.2 (95%CI: 2.0-9.0), having attained tertiary education, AOR=5.0 (95% CI: 2.4-9.8) and being in low socio-economic class, AOR=0.4 95% CI: 0.2-8.3). Determinants of good preventive practices included being less than 25 years, AOR=0.2 (95% CI: 0.1-0.8), having an interest in matters related to breast cancer, AOR=2.6 95% CI: 1.0-6.5) and attaining tertiary education, AOR=4.4 (95% CI: 1.0- 6.5). Conclusion: Women need to become more aware of breast cancer, especially those in younger age groups, low educational status, and poor socioeconomic class for early detection of breast cancer.